Impact of smart classroom preferences on critical thinking skills of chinese pre-service teachers: the role of moderating cognitive learning strategies - Roslan, Samsilah; Sulaiman, Tajularipin; Ma'rof, Aini Marina; Ni, Nie (UiTM Press, 2024)
This study aims to determine the influence of pre-service teachers’ preferences for smart learning environments on their critical thinking skills and moderating role of cognitive learning strategies. Critical thinking skills are essential for teachers as they enable them to analyse information, solve complex problems, and make informed decisions, ultimately enhancing their effectiveness in educating and guiding students. This quantitative study using multivariate analysis collected responses from preservice teachers from four colleges and universities in China. The sample size was 686 preservice teachers (M = 21 years, SD = 1.19 years; 65.6% female). SPSS v.26.0 was used to analyse the data. The results showed that there is a positive correlation between students’ preferences for smart classroom environment components and critical thinking skills. Moreover, the findings revealed that reflective thinking, inquiry-based learning, ease of use, and perceived usefulness influence the preservice teachers’ critical thinking skills. The results also showed that cognitive learning strategies significantly moderated their hypothesised associations. The results of the study can assist educators and curriculum designers in creating more challenging smart learning opportunities and evaluation systems.